Sistem Pendukung Keputusan Seleksi Pertukaran Mahasiswa Dalam Mendukung Kampus Merdeka Menerapkan Metode ROC dan TOPSIS - Assrani, Dwika; Triayudi, Agung; Simanjuntak, Handayani; Panjaitan, Fricia Oktaviani; Mesran, Mesran (Journal of Information System Research (JOSH), 2024)
The Indonesian Minister of Education, Nadiem Anwar Makarim, B.A., M.B.A. make a policy, namely an independent campus that strongly supports students in doing learning outside of campus in order to get new views of creative and innovative mindsets so that university graduates are expected to be able to compete in the world of work. In conducting the selection of student exchanges in supporting the independent campus, Budi Darma University is less effective, so to facilitate the student selection process in supporting the independent campus, a decision support system is needed in decision making, namely by using the Rank Order Centroid (ROC) method and the Technique For Orders Reference by Similarity to Ideal Solution (TOPSIS). The results of this study are the TOPSIS method, the best alternative is A4 for Desi Novria Siregar with a value of 1 and the lowest alternative is A6 for Fabyen Sabillah Chan with a value of 0.0645